PENGUJIAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG OLEH MAHKAMAH KONSTITUSI - Imbawani, Djoko (Jurnal Media Hukum, 2014)
Constitutional Court (MK) through Verdict Number 138/PUU-VII/2009 have, conclusionÂ  that authoritative MK to check, toÂ  judging, and breaking application of examination of Regulation of Government of Substitution of Code.Â  ThoughÂ  articleÂ  24Â  CÂ  sentenceÂ  (1)Â  Constitution ofÂ  IndonesiaÂ  StateÂ  1945Â  (IIIÂ  amendment)Â  forÂ  example authoritative testÂ  inviter codeÂ  toÂ  constitution,Â  to uphold supremacy of constitution. AssessmentÂ  toÂ  regulation ofÂ  government ofÂ  substitutionÂ  ofÂ  codeÂ  accordingÂ  toÂ  ruleÂ  articlesÂ  22Â  sentenceÂ  (2) Constitution ofÂ  Indonesia StateÂ  1945Â  conductedÂ  byÂ  ParliamentÂ  inÂ  nextÂ  conference.ThisÂ  ResearchÂ  typeÂ  isÂ  researchÂ  ofÂ  lawÂ  ofÂ  normative. Approach which utilized in this research is approach of law philosophy, approach of law theory, and constitutional approach. The system based on the Constitutionâs attempt to RIS or UUDS,Â  judicial it does not allow review of productÂ  in theÂ  form ofÂ  legislative act becauseÂ  the productÂ  is aÂ  result of the exercise ofÂ  sovereignty,Â  let alone judicialÂ  reviewÂ  againstÂ  a Perpu.Â  Similarly a Perpu born based onÂ  the ConstitutionÂ  of 1945Â  (originalÂ  text) also cannot be doneÂ  yudicialÂ  review. After he didÂ  theÂ  amendment toÂ  the Constitution process yudicial reviewÂ  can be done. Yudicial review against a Perpu can be done, butÂ  the need for the restriction that a Perpu substance shouldÂ  setÂ  things outsideÂ  theÂ  realm ofÂ  theÂ  Executive branchÂ  can doÂ  yudicial review.